2005
DOI: 10.1287/mnsc.1050.0368
|View full text |Cite
|
Sign up to set email alerts
|

What Actually Happened to the Inventories of American Companies Between 1981 and 2000?

Abstract: This paper examines the inventories of publicly traded American manufacturing companies between 1981 and 2000. The median of inventory holding periods were reduced from 96 days to 81 days. The average rate of inventory reduction is about 2% per year. The greatest reduction was found for work-in-process inventory, which declined by about 6% per year. Finished-goods inventories did not decline. Firms with abnormally high inventories have abnormally poor long-term stock returns. Firms with slightly lower than ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
321
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(346 citation statements)
references
References 10 publications
17
321
3
5
Order By: Relevance
“…This is the main claim of the paper and is consistent with the findings of Chen et al (2005): a 2% inventory reduction per year in the US between 1981 and 2000. Higher number of firms listed on the stock market during this period, 2 jointly with the improvements in operational technology explaining the great moderation phenomenon in the US (Blanchard and Simon, 2000), will generate reductions in inventory level.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is the main claim of the paper and is consistent with the findings of Chen et al (2005): a 2% inventory reduction per year in the US between 1981 and 2000. Higher number of firms listed on the stock market during this period, 2 jointly with the improvements in operational technology explaining the great moderation phenomenon in the US (Blanchard and Simon, 2000), will generate reductions in inventory level.…”
Section: Introductionsupporting
confidence: 89%
“…Hence, a steeper disinvestment in raw-material inventories is expected in comparison with final-good inventories. Consistent with this, Chen et al (2005), who analyzed the components of the overall inventory investment for the US between 1981 and 2000, showed that raw materials declined about 3% per year, whereas finishedgoods inventories did not decline at all. This is our second hypothesis to test: Hypothesis 2.…”
Section: Hypotheses To Contrastmentioning
confidence: 65%
“…Since the department editor information is available only from 2004, we exclude articles published during 2000-2003. 11 The early empirical papers were primarily concerned with examining inventory performance over time (e.g., Rajagopalan and Malhotra 2001;Chen et al 2005Chen et al , 2007. More recently, researchers have shifted toward establishing causal relationships between inventory and other operational variables.…”
Section: Endnotesmentioning
confidence: 99%
“…Additionally, changes in the inventory levels at a firm have been linked to an increase in the magnitude of the bullwhip effect experienced by partners upstream in a supply chain (Tangsucheeva & Prabhu, 2013). Although inventory reductions have the potential to both damage and improve firm performance, the preponderance of evidence in the literature suggests that shorter inventory holding periods (i.e., lower DIO) generally associate with improved liquidity and better firm financial performance (Capkun et al, 2009;Chen et al, 2005;Koumanakos, 2008;Swamidass, 2007). Further, it has been shown that excessive inventory levels are related to poor operational and financial performance (Singhal, 2005).…”
Section: Days Of Inventory Outstanding (Dio) and Firm Performancementioning
confidence: 99%